Fermentation and germination of pearl millet and cowpea : a review of nutritional quality, antinutritionalcompounds and functional properties - Gustavsson, Stina; Jacobsson, Sofia (SLU/Department of Molecular Sciences, 2020)
Undernutrition is responsible for 45% of deaths of children under the age of 5 in low- and middle-income countries, where pearl millet (Pennisetum glaucum) is one of the staple cereals. Despite of pearl millets favorable chemical composition, challenges still lie in the utilization of them due to the presence of antinutritional compounds (ANCs). Furthermore, combining pearl millet with a legume, such as cowpea, can improve the nutritional composition in a foodstuff. However, ANCs are also prevalent in legumes. The main ANCs in pearl millet and legumes are phytate and polyphenols. Furthermore, legumes also contain flatulence producing oligosaccharides. The aim of this study is to investigate the effect of fermentation and germination, by a literature review, on nutritional qualities, functional properties and ANCs in pearl millet and cowpea to then further be able to assess their qualities as components of weaning foods. In general, fermentation has shown a decrease in the carbohydrate content, an increase in protein content and contradictory results in the fat content of pearl millet. Fermentation of cowpea generally showed a decrease in carbohydrate content, no significant changes in the protein content and contradictory results in the fat content. Germination generally showed a decrease in carbohydrate content, an increase in the protein content and a decrease in the fat content of pearl millet and cowpea. Overall, a reduction in the ANC content (phytic acid, polyphenols and raffinose family oligosaccharides) was shown after fermentation and germination. Germination and fermentation resulted in decreases in bulk density, increase in oil absorption capacity (OAC) and increase in water absorption capacity (WAC) of the millet samples. Furthermore, viscosity was decreased by germination and increased after fermentation of the millet samples. The evaluated results showed positive changes in the chemical composition, ANC content and functional properties with the intention of producing weaning food. Further studies are needed to optimize the processing techniques, evaluate the combinatory effect of fermentation and germination as well as investigating the ideal ratio of pearl millet and cowpea in weaning foods.